Integration of QTL mapping and GWAS reveals the complicated genetic architecture of chemical composition traits in tobacco leaves - Ullah, Asad; Tong, Zhijun; Kamran, Muhammad; Lin, Feng; Zhu, Tianneng; Shahzad, Muhammad; Umaira,; Chen, Xuejun; Xiao, Bingguang; Xu, Haiming (Frontiers in Plant Science, 2025)
Tobacco (Nicotiana tabacum L.) is a significant industrial crop whose leaves serve as the primary raw material for various smoking products. However, the genetic basis of tobacco leaf chemical composition which is a key factor in product quality, remains largely unexplored. To address this, a QTL study was undertaken to pinpoint genomic loci associated with 21 leaf chemistry traits using a recombinant inbred line population of 271 genotypes evaluated across multiple environments. Variance components and heritability were estimated for nine multi-environment phenotypes. Phenotypic correlations between paired traits were calculated within each environment, while genotypic correlations were estimated across multi-environment phenotypes. Mixed-linear-model-based composite interval mapping (MCIM) was employed using QTLNetwork, leading to the identification of 18 QTLs with significant individual effects. Among these, qPA15-18 and qGA15-18 exhibited pleiotropic effects, while three epistatic QTL pairs associated with chlorogenic acid (CHA) and rutin (RU) were also detected. Notably, no significant QTL-by-environment interactions were observed. Through integration of association mapping, bioinformatics analysis and gene enrichment analysis of the QTL regions, we predicted three candidate genes. Nt08g00266 and Nt22g03479 were identified as pleiotropic genes associated with starch and total sugar, and with total sugar and reducing sugar, respectively. While, Nt16g00236 exhibited significant association with total plant alkaloid. This study lays the groundwork for tobacco varieties with enhanced chemical composition by targeting the identified QTLs and candidate genes, ultimately contributing to production of higher-quality smoking products.